A DOUBLE-EDGED SWORD OF CHATGPT IN STUDENTS’ WRITING PROCESS HIGHLIGHTING BENEFITS AND POTENTIAL DANGERS - Khairunisa, Hani; Novita Sari, Ratih (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
The integration of Artificial Intelligence (AI) like ChatGPT into education presents a double-edged sword for the student writing process. This research explores the benefits and potential dangers of using ChatGPT for writing exposition texts among senior high school students. Using a qualitative approach with an interpretative phenomenological analysis (IPA) design, this research collected data from ten XI.2 Inglan 2 students through in-depth interviews, observation, and document analysis. The findings reveal that ChatGPT is highly beneficial across all writing stages: assisting with idea generation and outlining in pre-writing, structuring paragraphs in drafting, and improving grammar and coherence during revision. However, two significant dangers were identified: a growing dependency that risks weakening students' critical thinking, and a loss of originality, as students felt their writing became